2016
DOI: 10.5720/kjcn.2016.21.4.354
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Diet and Nutritional Intake and Mortality Risk among South Korean Adults Based on 12-year Follow-up Data

Abstract: Objectives: Studies that reported the association between diet quality/nutritional intake status and mortality have rarely used long-term follow-up data in Asian countries, including Korea. This study investigated the association between the risk of mortality (all-cause and cause-specific) and the diet quality/nutritional intake status using followup 12-year mortality data from a nationally representative sample of South Koreans.Methods: 8,941 individuals who participated in 1998 and 2001 Korea Health and Nutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…1 % (SE), which were calculated by applying sampling weights assigned to individual participants in the nutrition survey and health examination. 2 p-values for % differences between urban and rural area were calculated using the chi-square test. 3 Including housewives or students.…”
Section: General Characteristics Between Urban and Rural Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 % (SE), which were calculated by applying sampling weights assigned to individual participants in the nutrition survey and health examination. 2 p-values for % differences between urban and rural area were calculated using the chi-square test. 3 Including housewives or students.…”
Section: General Characteristics Between Urban and Rural Participantsmentioning
confidence: 99%
“…According to the recent reports from the Global Burden of Disease Study in 2017, poor diet accounted for more than 50% of deaths and 66% of disability-adjusted life years [1]. A recent Korean study also confirmed that poor diet quality was associated with a higher mortality for all-cause, cardiovascular disease, and cancer, while using 12-year follow-up mortality data from a nationally representative sample [2].…”
Section: Introductionmentioning
confidence: 98%
“…However, according to our findings looking at BrCa, no significant relationship was observed. Also, in a study by Vargas et al, a higher DQI-I score was associated with a reduced risk of colorectal cancer [ 30 ], whilst in a 12 year follow-up study in South Korea, the results showed that higher MAR index was associated with a reduction in cancer and cardiovascular disease mortality by 66% and 98%, in those under 30 years of age and over 30 years of age, respectively [ 31 ]. However, in Arthur et al, inconsistent to our results, the authors reported that higher intake of Western diets and higher energy density (high consumption of red meat, processed meats, refined grains, high-fat dairy and desserts), compared the Mediterranean diet with lower energy density (high consumption of fruits, vegetables, whole grains, poultry, fish and legumes), was associated with an increased odds of hormone-dependent cancers [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition status was categorized by mean nutrient adequacy ratio [MAR(9)]. MAR(9) calculates the nutrient adequacy ratio (NAR) of nine nutrients (protein, calcium, phosphorus, iron, vitamin A, vitamin B1, vitamin B2, niacin, and vitamin C), adds them all together, and divides by nine [26]. A MAR(9) score of >0.75 was categorized as good and a score <0.75 was categorized as poor [27].…”
Section: Methodsmentioning
confidence: 99%